Nematic Phase of Plate-like Semicrystalline Block Copolymer Single Crystals in Solution Studied by Small-Angle X-Ray Scattering - Chi, Enyi (Langmuir : the ACS journal of surfaces and colloids, 2021)
Crystalline block copolymers have been used to prepare plate-like colloidal systems with well-controlled size, shape, and size distribution. The isotropic-to-nematic (I-N) phase transition of the novel plate-like colloidal particle suspensions has been reported previously. In this work, we focus on the characterization of the solution structure of the crystals and the N-phase using small- and ultrasmall-angle X-ray scattering techniques (SAXS/USAXS). The system has polystyrene-block-poly(l-lactide) (PS-b-PLLA) block copolymer single crystals (BCSCs) with different sizes dispersed in p-xylene. These crystals are truncated lozenge in shape and have effective diameters ranging from 550 to 4000 nm with a uniform dry thickness of 18.0 nm. Scattering of the individual crystal in solution can be simplified using a disc model with a core layer of 9-10 nm due to the lower contrast of the tethered PS layer. BCSC suspensions filled in thin quartz capillaries are prepared for monitoring the structural information. SAXS measurements of the isotropic phase show a strong face-to-face correlation, indicating that platelets form small stacked clusters in solutions. The isotropic phase is thus a coexistence of single crystals and the stacked multiple-layered clusters. The face-to-face spacing, d, in the N phases is around 75-90 nm, which increases slightly upon increasing the size of crystals. For a given system, the spacing does not change with increasing concentration under the current experimental conditions. Finally, the possible formation of lamellar domains within the N phase is also discussed due to the lateral attraction of this system. These results demonstrate the importance of the lateral attraction between the polar crystalline PLLA blocks on the formation of the N phase: the BCSCs self-assemble into larger sheets via the lateral attraction, which further enhances the I-N transition